OP0064 Drug Survival and Reasons for Discontinuation of Biological Therapy in 1679 Polyarticular Juvenile Idiopathic Arthritis Patients. (9th June 2015) - Horneff, G.; Huppertz, H.I.; Haas, P.; Tenbrock, K.; Minden, K.
Abstract : Objectives: To determine long term drug adherence and reasons for treatment discontinuation. Methods: Since 2001, JIA patients starting treatment with biologics have been followed by the Biologika in der Kinderrheumatologie (BIKER) registry. This database was screened for discontinuations of biological therapy. Results: 1679 polyarticular JIA pts were identified, 1190 treated with Etanercept, 372 Adalimumab, 69 Tocilizumab and 48 Abatacept. 892 had RF neg. polyarthritis (RFnegPA), 228 RF pos. polyarthritis (RFposPA) and 556 extended oligoarthritis (extOA). Treatment was discontinued in 764 pts. The frequency of discontinuation in pts with RFnegPA (422; 47.3%) was comparable to extOA (259; 46.6%), while it was lower in RFposPA (83; 36.3%; p=0.0019; Odds 0.625) compared to RFnegPA. The most common reason for disc. was inefficacy (283; 16.9%), followed by remission (223; 13.3%), intolerance (62; 3.7%) and others (51; 3.0%). In 145 (8.6%) cases the reason was not reported. No difference was found regarding the rate of inefficacy in either RFnegPA (16.8%), RFposPA (18.2%) or extOA (16.9%) and intolerance (4.1%; 2.6% and 3.4%, respectively), however patients with RFposPA (6.1%) less frequently disc. for remission than pts with RFnegPA (14.1%; p=0.00005; Odds 0, 324) or pts with extOA (14.9%; p=0.00069; Odds 0.373). Related to the total time of exposure, the rate of disc. was highest in extOA (14.4/100 patient-years [PY]) followed by RFnegPA (13.7/100 PY) and significantly lower in RFposPA (7.5/100 PY; p<0.0001, RR 0.55). 597 (50.2) patients disc. ETA, compared to 141 (37.9%) who disc. ADA, 10 (14.5%) TOCI and 16 (33.3%) ABA. Related to the total time of exposure, the rate of disc. was lowest in the TOCI cohort (8.3/100 PY) followed by ETA (12.1/100 PY), ADA (16.9/100 PY) and ABA (17.2/100 PY). Compared to ETA, the disc. rate of ADA was significantly higher (p<0.0005, RR 1.4). By Kaplan-Meier analysis drug survival of ETA, ADA and ABA was comparable but significantly prolonged for TOCI (p=0.01 compared to ETA, 0.007 to ADA. Remission led to disc. of ETA in 201 (16.9%), ADA in 21 (5.6%), TOCI in 1 (1.4%) and in none with ABA. Significantly more patients discontinued ETA in remission compared to other biologics (p=0.001; p=0.00068; and p=0.0003). Disc. rates of ADA due to inefficacy and intolerance was significantly higher compared to ETA. Conclusions: Most common reasons for discontinuation of biologics are inefficacy as well as remission. Marked differences between JIA categories and biologics used are found. Lowest rate of discontinuation is observed in RFposPA. Etanercept is more frequently discontinued due to remission and less frequently due to inefficacy than other biologics. Discontinuation due to intolerance is rare with all biologics. Disclosure of Interest: None declared